Efectividad de un programa educativo en el nivel de información en primigestas sobre cuidado del neonato - Barreto Báez, Kattya Yulissa (2016)
This research type quantitative, pre experimental, was carried out in health Center Victor Larco Herrera 25 primigestas in order to determine the effectiveness of the educational program "Ready to take care of my baby" in the level of information on care neonato in primigestas, so this is I used the Test Level of Information on Care Neonato, developed by Br. Lezema Vasquez Eleny Vanessa and Br. Melendez Prieto Ana Cecilia (2005) and modified by the authors as Pretest and Postest. For the analysis of variables I used the test T-student. Were found the following results: 84 percent of the primigestas obtained a mid-level information care postnatal before applied the educational program, 100 percent of the primigestas obtained a high level of information about care neonato after applied the educational program. The educational program "Ready to take care of my baby" is very highly significant. Is considered effective as the primigestas increased their level of information 85 percent accepted the hypothesis alternative (p = 0.000)